Project based CorelDRAW video tutorial enhancing embroidery ornament design competencies among fashion students - Fadhillah Riski Aisyah Nasution; Yuliarma Yuliarma; Weni Nelmira; M. Giatman; Nanda Sari Siregar; Alifah Biggum Nabila (Journal of Educational and Learning Studies, 2026)
This study aimed to develop and evaluate a project-based instructional video for embroidery ornament design using CorelDRAW to improve university students' practical competencies in vocational fashion education. A Research and Development approach employing the Four-D (4D) model (Define, Design, Develop, and Disseminate) was implemented. The product was validated by two media experts and three content experts, followed by practicality testing involving students and a lecturer. Effectiveness was examined using a one-group pretest-posttest design with 30 undergraduate students. Data were analyzed using Aiken's V, descriptive statistics, normalized gain, and paired-samples t-test. The instructional video demonstrated high validity and practicality and significantly improved students' learning outcomes, with a moderate N-gain and a significant difference between pretest and posttest scores (p < 0.001). The developed instructional video is a valid, practical, and effective digital learning resource for enhancing psychomotor competencies in embroidery ornament design